SEMANTICS AND PRAGMATICS OF EUPHEMISMS IN MODERN ENGLISH (Ustozlar uchun, 2026)
It will be covered in this article Euphemisms are widely used in modern English to soften harsh orsensitive expressions. Euphemism = polite/indirectexpression. Semantics = meaning, Pragmatics = use in context.From a semantic perspective, euphemisms keep the same meaningbut reduce emotional impact. “die” →  “passaway”, “unemployed” →  “between jobs”.From a pragmatic point of view, euphemisms depend on situation and intention.  “fired” →  “let go” is more polite in professionalcontexts.Euphemisms help maintain social harmony by avoiding directreference to sensitive topics. Used for illness, aging, anddisability.They also reflect cultural values and are common. “collateral damage” hides the harsh reality of civiliandeaths.